2008
DOI: 10.1110/ps.073330808
|View full text |Cite
|
Sign up to set email alerts
|

N15 Cro and λ Cro: Orthologous DNA‐binding domains with completely different but equally effective homodimer interfaces

Abstract: Bacteriophage Cro proteins bind to target DNA as dimers but do not all dimerize with equal strength, and differ in fold in the region of the dimer interface. We report the structure of the Cro protein from Enterobacteria phage N15 at 1.05 Å resolution. The subunit fold contains five a-helices and is closely similar to the structure of P22 Cro (1.3 Å backbone room mean square difference over 52 residues), but quite different from that of l Cro, a structurally diverged member of this family with a mixed a-helix/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…Further stepwise reduction, each with six nucleotides, was performed demonstrating that only a cro gene lacking at least 24 nucleotides did not mediate any DNA binding. Thus, the C-terminal amino acids of Cro are not essential for DNA binding, which matches the observation of Dubrava et al who reported for the closely-related N15 Cro repressor that five to seven C-terminal residues of its A and B chain are disordered [11]. By contrast, the region towards the N-terminus of the protein forms five alpha helices that are important for the recognition and binding of the target DNA and for the dimer interface.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Further stepwise reduction, each with six nucleotides, was performed demonstrating that only a cro gene lacking at least 24 nucleotides did not mediate any DNA binding. Thus, the C-terminal amino acids of Cro are not essential for DNA binding, which matches the observation of Dubrava et al who reported for the closely-related N15 Cro repressor that five to seven C-terminal residues of its A and B chain are disordered [11]. By contrast, the region towards the N-terminus of the protein forms five alpha helices that are important for the recognition and binding of the target DNA and for the dimer interface.…”
Section: Resultssupporting
confidence: 86%
“…In the enterobacterial telomere phages, immB encodes products related to the prophage repressor CB (prophage repressor CI in PY54), lytic repressor Cro, and a putative antiterminator Q as well as operator sites (three in N15 and ϕKO2, and one in PY54) located between cB and cro [8,10]. Due to the close relationship between the immB regions of N15 and ϕKO2, the same repressor target specificity for these phages has been suggested [1,11]. Indeed, using in vivo assays it has been shown that the genes for the prophage repressor, lytic repressor and Q of ϕKO2 influenced lysis and lysogeny of N15 in the same way as their counterparts of N15 [2,12].…”
Section: Introductionmentioning
confidence: 99%
“…The previously established crystal structures of the N15 Cro and λ Cro dimers are reproduced in Figure 1. 25, 26 Although the two complexes have similar molecular weights (N15 Cro, 17.8 kDa; λ Cro, 16.9 kDa), comparable interfacial contact areas (N15 Cro, 1303 Å 2 ; λ Cro, 1354 Å 2 ), and nearly equivalent dimer dissociation constants (N15 Cro, K D = 5 µM; λ Cro, K D = 3 µM), 26, 27 in a variety of other respects the dimers are strikingly unalike. The individual subunits of N15 Cro adopt an all α-helical fold and dimerize in a relatively superficial manner likened to “sticky billiard balls,” 28 whereby each subunit interacts with only outer surface side chains of the neighboring monomer (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Most particularly, several Cro proteins are known to have a classic five-helix repressor fold, while others, including λ Cro, have an unusual mixed α + β fold that is not known outside of this family and descended from the all-helical structure by a relatively continuous accumulation of small mutational events. 24,25 The change in fold completely remodels the dimer interface 24,26,42 and could easily modulate specificity through indirect readout. In this light, the fact that protein-DNA sequence correlations persist across the Cro family 7 and can be used to reengineer the specificity of λ Cro is quite remarkable and suggests that certain simple evolutionary recognition rules may survive major contextual changes during evolution.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cro proteins from phages N15 and λ have different global folds (all-α versus α + β, respectively) and no similarity in protein sequence. 26 Only three of seven base pairs are conserved between the two consensus O R halfsites. 7,27,28 The full O R sites also differ in symmetry properties, with the axis of pseudosymmetry for N15 lying between two base pairs and that for λ lying on one base pair.…”
Section: Introductionmentioning
confidence: 99%